PDGFRα+ Progenitor Cells Contribute to Muscle Fibroadipogensis Following Massive Rotator Cuff Tears in a Mouse Model. Issue 7 (18th July 2016) - Jensen, Andrew; Dar, Ayelet; Eliasberg, Claire; Kelley, Benjamin; Devana, Sai; McAllister, David R.; Petrigliano, Frank A.
Objectives: Rotator cuff tears affect an estimated 10% of patients over the age of 60, leading to significant activity related pain and decreased quality of life. After sustaining a tear, the rotator cuff musculature often undergoes muscle atrophy and fatty degeneration, which have been shown to result in poor clinical outcomes and high failure rates for surgical repairs. The cellular processes underlying these fibroadipogenic changes remain unknown although PDGFRβ+ cells have previously been implicated. Recently, it has been demonstrated in hind limb muscle that following acute, reversible injury via Cardiotoxin injection, PDGFRα-expressing cells are responsible for fibrotic and adipogenic muscle degeneration. Our study aimed to distinguish between the contribution of PDGFRα+ PDGFRβ+ cells and PDGFRα- PDGFRβ+ cells to fibroadipogenesis following massive rotator cuff tears. Methods: We performed supraspinatus tenotomy and denervation (TT+DN) operations on 8-10 week-old PDGFRβ-Cre x mTmG mice. These transgenic mice express GFP in cells co-expressing PDGFRβ, which allows PDGFRβ+ cell populations to be tracked via their GFP expression. At 5 days, 2-, 4- and 6-weeks postop, these mice and sham surgery controls were sacrificed and their supraspinatus muscles were harvested. We stained tissue sections with Oil Red O and Picro Sirius to compare levels of adipogenesis and fibrosis after TT+DN, respectively. In addition, sectioned muscle tissues were immuno-labeled with anti-PDGFRα and anti-PDGFRβ to assess differences in PDGFRα+ PDGFRβ+ cell localization. GFP expression was used to trace PDGFRβ cells and their progenies after TT+DN. Dissociated cells from supraspinatus tissue of TT+DN versus sham mice were either analyzed by flow cytometry for PDGFRα and GFP expression at established postop time points or sorted and cultured for in vitro differentiation experiments to assess the fibroadipogenic potential of these cell populations. Results: Oil Red O and Picro Sirius staining demonstrated that supraspinatus tissue reliably underwent significant fibroadipogenic changes that increased over time and were more pronounced 6 weeks following TT+DN. At 6 weeks following massive rotator cuff tears, PDGFRα+ GFP+ cells, GFP+ fibrotic tissue, and GFP+ adipocytes were detected in interstitial scar tissue (Fig. 1), indicating a contribution of PDGFRα+ PDGFRβ+ cells to fibroadipogenesis. Flow cytometry analyses revealed that the frequency of adipogenic PDGFRα+ sub-population was significantly increased 5 days postop and subsequently decreased to basal levels within 2 weeks. PDGFRα+ GFP+ cell populations were significantly more fibrogenic than other cell populations and increased fibrogenic potential was detected in PDGFRα cells from TT+DN mice in vitro (Table 1). Conclusion: PDGFRα+ fibroadipogenic progenitor cells directly contribute to post-injury rotator cuff fibroadipogenesis in a mouse model of massive rotator cuff tears. This cell population likely contributes to muscle atrophy and fatty degeneration of the rotator cuff in human pathology as well. With further development of clinical protocols, perioperative inhibition of this cell population or depletion of PDGFRα+ cells prior to cell transplantation in a regenerative treatment strategy may diminish fatty degeneration and improve clinical outcomes associated with rotator cuff tears.